2019
DOI: 10.1002/ceat.201800634
|View full text |Cite
|
Sign up to set email alerts
|

Residential Energy Supply Concept with Integration of Renewable Energies and Energy Storage

Abstract: Renewable energies are gaining importance in urban management and in the planning of new residential and mixed-use areas. Attention is also paid to selfsufficiency, as the public electrical grid is strained through the integration of renewables. Here, an energy supply concept for an urban residential area in the planning phase is discussed to meet both economic and ecologic criteria. Based on the demand, different technical options are analyzed. The integration of renewables is coupled with energy storage to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The required quantity and flow rate of H 2 for microgrid application for seasonal storage have been investigated previously, wherein 5.1 MT of H 2 was proposed to be stored as compressed gas at 45 bar. In the present study, we will assume that H 2 is produced during 5 months of summer for 8 h per day and is used during 3 months of the winter at 12 h per day.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The required quantity and flow rate of H 2 for microgrid application for seasonal storage have been investigated previously, wherein 5.1 MT of H 2 was proposed to be stored as compressed gas at 45 bar. In the present study, we will assume that H 2 is produced during 5 months of summer for 8 h per day and is used during 3 months of the winter at 12 h per day.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Specifically, while it is possible to dehydrogenate EtOH up to 90% conversion, the high conversion of EtOH would also favor the formation of Ru-OH from trace water to form the deactivated Ru-OAc species (see Figure S9 in the SI). 21 The required quantity and flow rate of H 2 for microgrid application for seasonal storage have been investigated previously, 32 wherein 5.1 MT of H 2 was proposed to be stored as compressed gas at 45 bar. In the present study, we will assume that H 2 is produced during 5 months of summer for 8 h per day and is used during 3 months of the winter at 12 h per day.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The stored hydrogen would be used to generate electricity in the winter using fuel cells when solar power cannot keep up with the demand. Such an approach has been investigated previously [101]. In this previous study, energy storage on the scale of 100 MWh was shown to meet the needs for a micro grid neighbourhood by storing ca.…”
Section: Lohcs For Seasonal Storagementioning
confidence: 99%
“…One potential application that has been investigated previously is the use of hydrogen in a microgrid application for seasonal storage [55]. In this study, 5.1 MT of hydrogen was proposed to be stored as compressed gas, which requires a total hydrogen storage volume of 1265 m 3 at 45 bar.…”
Section: Use Case Examplementioning
confidence: 99%